APLIKASI INFLOW CONTROL DEVICE (ICD) PADA SUMUR HORIZONTAL UNTUK OPTIMASI PRODUKSI - Surya Perdhana, Alfa
Horizontal well is one of the methods in the petroleum industry in an effort to improve the acquisition and life time of a field. Horizontal well can increase the acquisition and the life time of a field because it has large contact area and has the ability to sweep better than vertical well. This advantages are very appropriate when applied in a thin reservoir or so-called oil rim. However, horizontal wells also have shortcomings, particularly in the oil reservoir rim, the magnitude of the possibility of coning, both gas and water. Coning will make oil production decreased due to gas or water that would be produced reduce the volume of oil production in the wellbore. In the oil reservoir, the reservoir there are several conditions that cause coning and early gas and water breakthrough, that is the reservoir conditions with heterogeneous permeability. Additionally coning and early gas and water production occur because the phenomenon heel-to-toe effect, where the largest friction on heel of the well resulted in a great decreasing of pressure in the well. In this final project we will see the application of ICD (Inflow Control Device) at reservoir conditions that have heterogeneous permeability by means of simulations using reservoir modeling software, especially in making a uniform flow of oil and gas along the horizontal hole thus increasing the final recovery of oil wells. Issue is being simplified only gas coning problem, so it can be seen that ICD functions as gas production control. The results of the sensitivity simulations suggest a link between ICD configuration used as the number of ICD and ICD nozzle size diameter of the condition of the reservoir permeability.